Water demand management: shifting urban water management towards sustainability - Sam Kayaga; Ian Smout; Hana Al-Maskati (2007)
Whereas the world population is increasing at a high rate, especially in urban areas, the water resources have not only remained constant, but they are being polluted at a high rate, which inevitably results in fresh water scarcity. Current urban water management concepts and practices cannot adequately respond to these changes. There is need for water professionals to change the way they manage water resources in urban areas if we are to ensure economic and environmental sustainability. In addition to consideration of supply-side options, we need to apply water demand management (WDM) tools both on the utility and end-user sides. This paper describes the basic concepts of WDM, provides a case study of their application in Bahrain, and briefly introduces the five-year EU-funded SWITCH Project that aims at creating a paradigm shift in urban water management practices